Review paper: Enhancing manufacturing flexibility implementation through industry 4.0 technology - Mohd Ghazali, Maarof; Gusman, Nawanir; Muhammad Fakhrul, Yusuf (Academia Industry Networks, 2022)
The current business environment is often characterized by dynamic market environment. This dynamic market which caused uncertainty in the market demand was due to globalization, fierce market competition, and advancement in the technology. Such uncertainty requires some sort of internally based flexibility known as manufacturing flexibility. This research paper discussed on manufacturing flexibility and investigated how industry 4.0 technology can help manufacturing firms to become more flexible. A review research approach based on past studies have been employed in this study. The main body of this review is based on two sources of database, SCOPUS, and Google Scholar. Manufacturing flexibility is a concept known to equipped businesses to confront with market uncertainties and finding the right match between product’s specification and market needs. Thus, it is used by businesses to become more flexible and dynamic in its operation. Advancement in technology such as industry 4.0 bring new hopes for manufacturers to operate in a more flexible operation. Nine technologies under the umbrella of industry 4.0 have been discussed in this research. Future studies should conduct in-depth qualitative approach to study how industry 4.0 technology can help to enhance manufacturing flexibility implementation in the manufacturing industry. Furthermore, there is also needs to conduct analysis of other contributing factors that can contribute to implementing manufacturing flexibility especially those that focused on the developing countries. The result from this research is expected to provide guidance for manufacturers to implement manufacturing flexibility more effectively in their firm.